Membranes for Energy Conversion 2007
DOI: 10.1002/9783527622146.ch5
|View full text |Cite
|
Sign up to set email alerts
|

Composite Membranes for High Temperature Direct Methanol Fuel Cells

Abstract: A low cost and high temperature membrane, with suitable ionic conductivity and stability up to 150 8C, would be a potential solution to some of the drawbacks presently affecting reformate-fuelled polymer electrolytes (PEMFCs) as well as direct methanol fuel cells (DMFCs) [1][2][3][4][5][6][7]. Fuel cell operation at elevated temperatures can limit the effects of electrode poisoning by adsorbed CO molecules, increase both methanol oxidation and oxygen reduction kinetics and simplify water and thermal management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…A rational analysis of filler effects on structural, proton transport properties and the electrochemical characteristics of composite perfluorosulfonic membranes for DMFCs was reported [107,125]. It was observed that a proper tailoring of the surface acid-base properties of the inorganic filler for application in composite Nafion membranes allows appropriate DMFC operation at high temperatures and reduced pressure [107].…”
Section: Membranes For High Temperature Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A rational analysis of filler effects on structural, proton transport properties and the electrochemical characteristics of composite perfluorosulfonic membranes for DMFCs was reported [107,125]. It was observed that a proper tailoring of the surface acid-base properties of the inorganic filler for application in composite Nafion membranes allows appropriate DMFC operation at high temperatures and reduced pressure [107].…”
Section: Membranes For High Temperature Applicationsmentioning
confidence: 99%
“…It was observed that a proper tailoring of the surface acid-base properties of the inorganic filler for application in composite Nafion membranes allows appropriate DMFC operation at high temperatures and reduced pressure [107]. An increase in both the strength and amount of acidic surface functional groups in the fillers enhances water retention inside the composite membranes through an electrostatic interaction in the presence of humidification constraints, in the same way as for the adsorption of hydroxyl ions in solution [107,109,125].…”
Section: Membranes For High Temperature Applicationsmentioning
confidence: 99%
“…Aricó's group in Italy have studied Nafion composite membranes and other polymers aiming to find low cost membranes with suitable proton conductivity and stability up to 150 C for high temperature DMFC [6]. Nafion composites with SiO 2 , ZrO 2 , Al 2 O 3 , and SiO 2 /PWA [315] exhibit maximum in conductivity at about 135 C, that is, a 15 C higher that the corresponding pure Nafion recast membrane, as shown in Fig.…”
Section: Proton Conductivitymentioning
confidence: 99%
“…6.20) [6,95,96]. Important conductivity increases were also obtained using sulfonated mesostructurated silica (MSU-F and MCM-41) [44], and silica nanoparticles with a sulfonated oligomer layer [50], as shown in Fig.…”
Section: Proton Conductivitymentioning
confidence: 99%
See 1 more Smart Citation